Blood lactate time course changes from high-speed exercise - Caruso, J. F.; Mason, M. L.; Borgsmiller, J. A.; Barbosa, A. G.; Gutierrez, E. V. (Medicina Sportiva, 2014)
Introduction: Post-workout blood lactate concentration ([BLa-]) values aid training prescriptions for athletes. Objective: To compare changes of [BLa-] from two workouts, each comprised solely of repetitions that either entailed intermittent (phasic) or continuous (tonic) force exertion, done by competitive (n = 47) and novice (n = 26) athletes. Methods: Workouts were performed on a high-speed exercise device using the athlete`s left arm. Per exercise bout [BLa-] values were measured pre- as well as at zero, five, ten, 15 and 20 minutes post-exercise. Total work (TW) values for each gender-workout-training status assignment were assessed with a 2x2x2 ANOVA with repeated measures for workout. [BLa-] data were compared with a 2(gender) x 2(workout) x 2(training status) x 6(time) ANOVA with repeated measures for workout and time. Results: TW had a two-way interaction, as the tonic bout done by competitive athletes evoked higher values than the other assignments. Inter-gender (male > female) TW differences occurred for the competitive group; none occurred for novices due to higher variability from the limited number of novice males. [BLa-] values yielded numerous significant gender x workout x training status differences over the time points examined. Conclusions: Temporal [BLa-] changes saw competitive athlete values rise sharply from zero to five minutes post-workout, while novice values changed little over the same time interval. This implies post-workout [BLa-] were impacted by the TW performed. Temporal differences regarding the time peak post-workout [BLa-] values occur may aid the design of divergent training prescriptions for competitive and novice athletes.